REAKSI KINETIS PEMECAHAN MINERAL ILMENIT PADA SINTESA TiO2 DENGAN H2SO4 - Zuhdi Ma’sum; Taufik Iskandar (Universitas Tribhuwana Tunggadewi, 2009)
Titanium diokside (TiO2) is widely used in chemical industries, especially in ceramics industries. It could be produced by destructing of the ilmenite mineral with sulfuric acid. The design process of destruction needs mathematical modeling which is similar to heterogeneous system that involves both mass transfer and chemical reaction simultaneously. The reaction between the ilmenite mineral and sulfuric acid was conducted in a stirred-batch reactor. The ilmenite mineral and sulfuric acid were mixed in the reactor then it was closed. The reactor was heated and stirred at a certain stirring rate until desired temperature was reached. Samples were withdrawn every 10 minutes. The variables studied were the reaction temperature in the tange of 383 K and 403 K and the rate of stirring in the range of 60 and 125 rpm. There were two proposes models. The first model was a shrinking-core mixed chemical-dynamic regime model. The second model was a shrinking-core chemical regime model. Based on the results, the first model was the suitable model of the two models proposed for describing the kinetics phenomena of the destruction of ilmenite mineral with sulfuric acid. From this model it was obtained that the value of reaction rate constant (kr) could be approached by the Arrhenius equation, as the following; kr = 8,59.1019.e-44578/(RT), in which R is the gas constant and T is the absolute temperature. It was obtained that the value of mass transfer coefficient was not significantly influenced by the rate of stirring